I’m not Welcome Here – Uma Revisão de Escopo sobre Toxicidade e Discurso de Ódio em Jogos Digitais - Gibrim, Paula Teresa M.; Ribeiro, Marcus Vinicius Guerra; Moreira, Lorena Souza; Melo, Philipe de F.; Reis, Julio C. S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.15998, 2025)
Hate speech and toxic behaviors are increasingly common in digital games, affecting player wellbeing, diversity and community engagement. Although research on this topic has increased in recent years, studies remain fragmented and largely focused on the North American and European contexts. This study presents a scoping review of the scientific literature on hate speech in games, covering publications from 2010 to 2025, including international and Brazilian research. A search of four electronic library sources, complemented by manual searches, retrieved 8,040 records. After filtering and screening using predefined criteria, 49 studies were selected for full-text analysis. The review presents the investigated associations, detection approaches and intervention strategies, consolidates the scattered results and identifies areas for further investigation. Among these observations is the relative scarcity of research focused on Brazilian gaming communities, suggesting opportunities for more regionally contextualized studies in the future.